Influence of Hypoxic Preservation Temperature on Endothelial Cells and Kidney Integrity. (4th June 2019) - Giraud, Sébastien; Steichen, Clara; Couturier, Pierre; Tillet, Solenne; Mallet, Vanessa; Coudroy, Rémi; Goujon, Jean-Michel; Hannaert, Patrick; Hauet, Thierry
Abstract : Ischemia-reperfusion (IR) injury is unavoidable during organ transplantation and impacts graft quality. New paradigms are emerging including preservation at higher temperature than "hypothermia" or "cold": although 4°C remains largely used for kidney preservation, recent studies challenged this choice. We and others hypothesized that a higher preservation temperature, closer to physiological regimen, could improve organ quality. For this purpose, we used an in vitro model of endothelial cells exposed to hypoxia-reoxygenation sequence (mimicking IR) and an ex vivo ischemic pig kidneys static storage model. In vitro, 19°C, 27°C, and 32°C provided protection against injuries versus 4°C, by reducing cell death, mitochondrial dysfunction, leukocyte adhesion, and inflammation. However, ex vivo, the benefits of 19°C or 32°C were limited, showing similar levels of tissue preservation damage. Ex vivo 4°C-preserved kidneys displayed a trend towards reduced damage, including apoptosis. Macrophage infiltration, tubulitis, and necrosis were increased in the 19°C and 32°C versus 4°C preserved kidneys. Thus, despite a trend for an advantage of subnormothermia as preservation temperature, our in vitro and ex vivo models bring different insights in terms of preservation temperature effect. This study suggests that temperature optimization for kidney preservation will require thorough investigation, combining the use of complementary relevant models and the design of elaborated preservation solution and new technologies.